Association between preoperative aspartate aminotransferase-to-platelet ratio index and prognosis in colorectal liver metastases: a systematic review and meta-analysis - Li, Huiwen; Yin, Yuanyuan; Yang, Zongliang; Ding, Ning; He, Yongheng (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: This study intended to examine the predictive ability of the preoperative aspartate aminotransferase-to-platelet ratio index (APRI) for the prognosis of individuals with colorectal liver metastases (CRLM) undergoing surgical resection. We aimed to evaluate the associations of APRI with overall survival (OS), progression-free survival (PFS), and postoperative complications to offer a reference for preoperative risk stratification.Methods: The protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) (registration number: CRD420251058027). PubMed, EMBASE, Web of Science (WOS), and Cochrane were retrieved from inception to April 23, 2025. Quantitative synthesis was restricted to homogeneous surgical cohorts to minimize clinical heterogeneity. Meta-analysis was carried out leveraging STATA 15.1 and Meta-Disc 1.4.Results: In total, 10 studies were incorporated for systematic review. The meta-analysis of surgical cohorts revealed that a higher preoperative APRI tended to be associated with reduced OS [hazard ratio (HR) =1.14, 95% confidence interval (CI): 1.01–1.28, P